2007
DOI: 10.1121/1.2749716
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic variability within and across German, French, and American English vowels: Phonetic context effects

Abstract: Cross-language perception studies report influences of speech style and consonantal context on perceived similarity and discrimination of non-native vowels by inexperienced and experienced listeners. Detailed acoustic comparisons of distributions of vowels produced by native speakers of North German (NG), Parisian French (PF) and New York English (AE) in citation (di)syllables and in sentences (surrounded by labial and alveolar stops) are reported here. Results of within- and cross-language discriminant analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 37 publications
(29 reference statements)
2
85
0
1
Order By: Relevance
“…In other words, they may have simply been drawing upon vowel tokens that were already in their repertoire: particularly fronted versions of English /u/. It has been proposed that due to the fact that American English /u/, which is already relatively front on average, is further fronted in the context of alveolars, the front vowel /y/ may not actually constitute a "new" vowel for English-speaking L2 learners, but instead a "similar" vowel, at least in the context of alveolars (Strange et al, 2007;Levy, 2009;Levy and Law, 2010). Documented perceptual assimilation patterns in which English speakers identify German and French /y/ as closest to English /u/ (e.g.…”
Section: B "New" Vs "Similar" Categoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, they may have simply been drawing upon vowel tokens that were already in their repertoire: particularly fronted versions of English /u/. It has been proposed that due to the fact that American English /u/, which is already relatively front on average, is further fronted in the context of alveolars, the front vowel /y/ may not actually constitute a "new" vowel for English-speaking L2 learners, but instead a "similar" vowel, at least in the context of alveolars (Strange et al, 2007;Levy, 2009;Levy and Law, 2010). Documented perceptual assimilation patterns in which English speakers identify German and French /y/ as closest to English /u/ (e.g.…”
Section: B "New" Vs "Similar" Categoriesmentioning
confidence: 99%
“…The segmental context in which a vowel occurs-in particular, the place of articulation of flanking consonants-has been shown to have a significant, predictable effect on the quality of the vowel. American English /u/, for example, has been shown to be significantly fronted in the context of alveolars (Hillenbrand et al, 2001;Strange et al, 2007). Place of articulation has also been shown to have a predictable effect on VOT (e.g.…”
Section: B "New" Vs "Similar" Categoriesmentioning
confidence: 99%
“…However, we had also recorded the speaker " s production of English vowels in the disyllable /hVb=/ (real words were used to aid in pronouncing vowels with ambiguous spelling), and formant values averaged over three tokens indicated that the speaker did not differentiate between English /e/ in hebba (F1 572 Hz, F2 1934 Hz) and /ae/ in habba (F1 586 Hz, F2 1914 Hz). Since /e/, but not /ae/, is an existing phoneme in the Dutch speaker's native repertoire, and the observed formant values better match the citation style values for English /e/ than for /ae/ (see e.g., Ladefoged, 1993;Strange et al, 2007), it is more likely, however, that the Dutch speaker indeed produced a vowel that was closer to /e/ than to /ae/ (and the authors who selected the best tokens of the recordings of course also perceived it like that).…”
Section: Experiments 1bmentioning
confidence: 99%
“…The variation in responses between contexts in the discrimination task was not predicted by the PAM-L2, as it posits a level of representation where such detail is not encoded after categorization occurs. The ASP provides a framework in which to investigate not only differences in syllable or word position, as in the current study, but also to examine effects of coarticulation or the context of the overall utterance (e.g., in isolation, in a sentence; Nishi, Strange, AkahaneYamada, Kubo, & Trent-Brown, 2008;Strange et al, 2005;Strange et al, 2007). In the discrimination task, the general greater sensitivity to pharyngeal pairs over uvular pairs by L2 speakers was predicted by the ASP but not by the PAM-L2.…”
Section: Fixed Effectsmentioning
confidence: 99%